BIOMEDICAL WASTE MANGEMENT IN THE DISTRICT OF BALASORE, ODISHA :A CRITICAL SURVEY: Life Science-Environmental sciences - CHANDRA SAHOO, RAMESH; SAHOO, DEBASHRITA; SAHOO, JHARANA; CHANDRA PRADHAN., SUNAND (International Journal of Life Science and Pharma Research, 2013)
Biomedical waste has become a serious health hazard irrespective of states & nations worldwide. Careless and indiscriminate disposal of this waste by healthcare establishments and research institutions can contribute to the spread of serious diseases such as hepatitis and AIDS (HIV) among those who handle it and also among the general public. The present study pertains to the biomedical waste management practices at various Hospitals in the district of Balasore, odisha. The study shows that infectious and non-infectious wastes are dumped together within the hospital premises, resulting in a mixing of the two, which are then disposed of with municipal waste at the dumping sites in the city. All types of wastes are collected in common bins placed outside the patients wards. For disposal of this waste the hospital depends on the generosity of the Balasore Municipal Corporation, whose employees generally collect it every 2 or 3 days. The hospitals do not have any treatment facility for infectious waste. The laboratory waste materials, which are disposed of directly into the municipal sewer without proper disinfection of pathogens. All disposable plastic items are segregated by the rag pickers from the hospital as well as municipal bins and dumps. The waste is deposited either inside the hospital grounds, or outside in the community bin for further transportation and disposal along with municipal solid waste. The open dumping of the waste makes it freely accessible to rag pickers who become exposed to serious health hazards due to injuries from sharps, needles and other types of material used when giving injections. The results of the study demonstrate the need for strict enforcement of legal provisions and a better environmental management system for the disposal of biomedical waste in the Hospitals, as well as other healthcare establishments in Balasore, Odisha.